The mediating effect of problem-focused coping on the relationship between emotional clarity and mental health among older adults - Cho, Myung Hyun; Choi, Kee-Hong (Frontiers in Behavioral Neuroscience, 2024)
Objective Individuals who can recognize emotions well are better able to identify and accept their feelings and manage them. This study examined the mediation of problem-focused coping in the pathway through which emotional clarity predicts higher life satisfaction and lower depression in older adults. Methods In total, 150 older adults (75 male and 75 female, aged 60–69 years, with a mean of 64.53 [SD = 2.49]) participated in a face-to-face survey, answering questions on emotional clarity, problem-focused coping, life satisfaction, and depression. Results Emotional clarity was associated with higher life satisfaction and lower depression in older adults. People who were aware of their emotions well were in better emotional condition. Mediation analysis revealed that problem-focused coping mediated the positive relationship between emotional clarity and life satisfaction and the negative relationship between emotional clarity and depression. Older adults who understand their own emotions tend to deal with emotional events in a problem-focused manner, leading to high life satisfaction and low depression. Conclusion This study identifies cognitive conditions for increasing life satisfaction and preventing depression in later life and offers suggestions for personal and social efforts to maintain mental health.